2020
DOI: 10.1002/jlb.3mr0120-203rr
|View full text |Cite
|
Sign up to set email alerts
|

Erdheim-Chester disease: An in vivo human model of Mϕ activation at the crossroad between chronic inflammation and cancer

Abstract: Erdheim-Chester disease (ECD) is a rare histiocytosis characterized by infiltration of multiple tissues by CD68 + foamy M s (or 'histiocytes'). Clinical manifestations arise from mass-forming lesions or from tissue and systemic inflammation. ECD histiocytes harbor oncogenic mutations along the MAPK-kinase signaling pathway (BRAF V600E in more than half of the patients), and secrete abundant pro-inflammatory cytokines and chemokines. Based on these features, ECD is considered an inflammatory myeloid neoplasm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Moreover, its expression was upregulated during different histiocytoses, e.g. LCH [ 18 , 42 ] and Erdheim-Chester disease [ 43 ]. Additionally, the mesenchymal stromal cells (MSCs) themselves are also capable of expressing HLA DR [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its expression was upregulated during different histiocytoses, e.g. LCH [ 18 , 42 ] and Erdheim-Chester disease [ 43 ]. Additionally, the mesenchymal stromal cells (MSCs) themselves are also capable of expressing HLA DR [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 1 ) reported that ECD histiocytes harbor oncogenic mutations in genes involved in the MAPK, signaling pathway (BRAF V600E in more than half of the patients) and secrete abundant proinflammatory cytokines, such as interleukin (IL)-1, IL-6, and TNF-α, as well as chemokines. Based on these features, ECD is considered an inflammatory myeloid neoplasm ( 1 , 6 ). In recent years, ECD was added to the classification of histiocytic and dendritic cell neoplasms ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocytosis. ECD is considered an inflammatory myeloid neoplasm whose pathogenesis is related to BRAF V600E mutation or other mutations in the MAPK pathway ( 1 ). It is a multisystem disease involving all organs, and intestinal involvement is even rarer.…”
Section: Introductionmentioning
confidence: 99%
“…The system was suitable to investigate the impact of drugs, including therapeutic mAbs. Specifically, 3D cultures of tissue biopsies derived from patients affected by Erdheim Chester Disease (ECD), a rare inflammatory myeloid neoplasm driven by MAPK mutations (particularly the BRAF V600E mutation) [ 107 , 108 ], allowed to unveil immune-metabolic mechanisms underlying disease pathogenesis and to compare the efficacy of IFX versus the specific BRAF-inhibitor vemurafenib in dampening inflammation [ 103 ]. Culture in bioreactor of fresh tissue explants (organotypic culture) allows assessment of the dynamic evolution of tumor angiogenesis through serial sampling followed by histological and image analysis of tumor features (e.g., nuclei, stroma and angiogenic CD34 + vessels).…”
Section: Exploiting 3d Models For Therapeutic Mab Testingmentioning
confidence: 99%